2015
DOI: 10.1080/13691058.2015.1053413
|View full text |Cite
|
Sign up to set email alerts
|

Why do men often not use condoms in their relationships with casual sexual partners in Uganda?

Abstract: With a focus on Uganda, this paper examines men's condom use in sexual relationships with casual partners and what this might tell us about men's vulnerability to HIV-infection. We carried out repeat interviews with 31 men attending a clinic serving women at high risk for HIV infection and their partners in Kampala. We found that the experience of condom-less sex in the men's youth, itself the outcome of a restrictive home environment, was perceived as influencing later unsafe sexual behaviour. Peer pressure e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 51 publications
5
19
0
Order By: Relevance
“…This is consistent with other studies done elsewhere [33]. Special training programs on condom use and on negative attitudes about gender norms have been reported to be effective in reducing condom failure and HIV prevalence in some FSWs communities [33,[34][35][36]. The study participants reported that often times, efforts to stop men to continue sex after condom failure failed.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with other studies done elsewhere [33]. Special training programs on condom use and on negative attitudes about gender norms have been reported to be effective in reducing condom failure and HIV prevalence in some FSWs communities [33,[34][35][36]. The study participants reported that often times, efforts to stop men to continue sex after condom failure failed.…”
Section: Discussionsupporting
confidence: 90%
“…The practice of having multiple sexual partners, as a demonstration of a man's masculinity, a practice associated with high risk behaviour, may affect the uptake and consequently HIV protection (Allison & Seeley, 2004;Kissling et al, 2005;Mojola, 2011). We have found in similar settings that men are reluctant to use condoms even with casual partners (Rutakumwa et al, 2015); faith in the efficacy of circumcision to provide protection, may make condom use even less likely (Andersson et al, 2011;Hallett et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
“…Such relationships are shaped by dominant masculine norms which place the man firmly in control. The desire for greater sexual pleasure or children, and the concern to validate trust in a relationship means that condom use is forgotten in these sexual relationships, resulting in an increased risk of HIV-infection (Aho, Koushik, & Rashed, 2012;Goldenberg et al, 2010;Matovu & Ssebadduka, 2014;Murray et al, 2007;Rutakumwa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%